Smith & Tanagho's general urology - McAninch, Jack W.; Lue, Tom F. (New York : McGraw-Hill Education, 2020)
"Smith & Tanagho's General Urology, Nineteenth Edition offers a complete overview of the diagnosis and treatment of the diseases and disorders managed by urologic surgeons. This trusted classic delivers a clear, concise presentation of the etiology, pathogenesis, clinical findings, differential diagnosis, and medical and surgical treatment of all major urologic conditions. The well-organized, user-friendly design makes relevant clinical information and management guidelines easy to find and simple to implement."--Publisher's description.
Anatomy of the genitourinary tract -- Embryology of the genitourinary system -- Symptoms of disorders of the genitourinary tract -- Physical examination of the genitourinary tract -- Urologic laboratory examination -- Radiology of the urinary tract -- Vascular interventional radiology -- Retrograde instrumentation of the urinary tract -- Percutaneous endourology and ureterorenoscopy -- Laparoscopic surgery -- Robotic surgery in urology -- Urinary obstruction & stasis -- Vesicoureteral reflux -- Bacterial infections of the genitourinary tract -- Specific infections of the genitourinary tract -- Sexually transmitted infections -- Urinary stone disease -- Injuries to the genitourinary tract -- Urothelial carcinoma: cancers of the bladder, ureter, and renal pelvis -- Renal parenchymal neoplasms -- Cancer of the prostate gland -- Genital tumors -- Urinary diversion and bladder substitutions -- Systemic therapy of urologic tumors -- Immunotherapy in urologic malignancies -- Radiotherapy of urologic tumors -- Neurophysiology and pharmacology of the lower urinary tract -- Neurogenic bladder -- Urodynamics -- Urinary incontinence -- Disorders of the adrenal glands -- Disorders of the kidneys -- Diagnosis of medical renal diseases -- Acute kidney injury and oliguria -- Chronic kidney disease and renal replacement therapy -- Renal transplantation -- Disorders of the ureter and ureteropelvic junction -- Disorders of the bladder, prostate, and seminal vesicles -- Male sexual dysfunction -- Women's sexual health -- Disorders of the penis and male urethra -- Disorders of the female urethra -- Disorders of sex development -- Male infertility -- The aging male -- Genital gender-affirming surgery: patient care, decision making, and surgery options -- History and physical examination in pediatric urology -- Introduction to clinical research design.
"A LANGE medical book."
Revised edition of: Smith & Tanagho's general urology / edited by Jack W. McAninch, Tom F. Lue. 18th ed. ©2013.
Includes bibliographical references and index.
Keywords: Urologic Diseases